2016
DOI: 10.21276/ijlssr.2016.2.5.14
|View full text |Cite
|
Sign up to set email alerts
|

The Awareness of Folic Acid Supplements among Women of Child bearing Age in King Abdulaziz University Hospital, Jeddah-Saudi Arabia

Abstract: ABSTRACT-This study aimed to assess the awareness of the importance of folic acid in preventing neural tube defects (the timing of folic acid supplementation and the right doses) in Jeddah the western region of Saudi Arabia. A sample of 501 married women in the reproductive age (19-45 years) who visited the outpatients clinics at King Abdulaziz University Hospital between August and October/2015 were asked to participate in a survey study targeting the awareness and the use of folic acid before and during preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
4
1
2
1
Order By: Relevance
“…However, this study reports a comparatively higher intake of FA supplementation during pregnancy or pregnancy planning than previous studies from Saudi Arabia 20 , 21 , 34 and other countries that reported low percentages of FA supplementation intake in their study population, especially during the periconceptional period. 35 38 Knowledge pertaining to the proper timing of FA supplements is absolutely essential to ensure the normal development of the nervous system in infants, and to minimize the risk of NTDs.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…However, this study reports a comparatively higher intake of FA supplementation during pregnancy or pregnancy planning than previous studies from Saudi Arabia 20 , 21 , 34 and other countries that reported low percentages of FA supplementation intake in their study population, especially during the periconceptional period. 35 38 Knowledge pertaining to the proper timing of FA supplements is absolutely essential to ensure the normal development of the nervous system in infants, and to minimize the risk of NTDs.…”
Section: Discussioncontrasting
confidence: 93%
“…25 In this study, although awareness of FA was high among the respondents, the usage of FA supplementation reported by respondents was low. Similar findings were reported by studies conducted in Saudi Arabia 20,21,34 and other countries. [35][36][37][38] The present findings suggest that respondents with specialization in health sciences gained knowledge through education, which helped to improve the intake of FA supplements.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study found that more than half of the participants knew the importance of folic acid in preventing neural tube formation and promoting brain and spinal cord growth, which was consistent with a previous study in Saudi Arabia that showed that 54.5% of the participants were familiar with the usefulness of folic acid in preventing these abnormalities 24 . However, the findings of our study were lower than that of other studies that reported a higher level of awareness about the role of folic acid in preventing these abnormalities 25,27,28 . In the study conducted in King Fahad Medical City, a higher level of awareness was reported, in which 80.1% of women were aware that folic acid is used to prevent NTDs 24 .…”
Section: Discussioncontrasting
confidence: 90%
“…Hence regarding correct knowledge on this vitamin and its association with educational level, our results are consistent with the findings of similar studies done in Makkah Al-Mokarramah, Saudi Arabia (72.2%), Tabuk, Saudi Arabia (48.5%), Lebanon (24.7%), [19,20,21,22], and in Qatar (41.3%), where most of women who knew and used Folic acid before the pregnancy and during the first trimester, were those having higher education level [23]. Likewise, similar study in Texas (USA) showed a significant association ( ≤ 0.001) of level of awareness with education level [24].…”
Section: Discussionsupporting
confidence: 91%